THE RELATIONSHIP BETWEEN STUDENTS’ SELF-EFICACY AND THEIR SPEAKING ENGLISH PROFICIENCY - Iva Yuanita Andriani; Alfan Zuhairi; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstractThis recent study purposed to investigate the relationship between students’ self-efficacy and their speaking performance in learning English. This investigation employed 60 students of English Education Department at University of Islam Malang in the fourth semester. For the research design, descriptive quantitative method was applied. The procedure of collecting data in this research involved two steps; distributing self-efficacy questionnaires to the 60 participants and then testing the students speaking proficiency through performing their professional biographies (CV). Lastly, the data collection was then analyzed and computed using Pearson Product Correlation of SPSS 20. The finding of this research indicated that there is no relationship between the students’ self-efficacy and their speaking performance as it was obtained that the r critical > r table (r critical= 0.013 > r table= 0.05). Based on the finding of this research, it is addressed to the readers that self-efficacy is not the determination the students’ speaking English proficiency.Keywords: self-efficacy, speaking performance, oral presentation.